2005
DOI: 10.1021/jo051811u
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Acyl Anion Equivalents from Acylphosphonates via Phosphonate−Phosphate Rearrangement:  A Highly Practical Method for Cross-Benzoin Reaction

Abstract: [reactions: see text] Acylphosphonates are potent acyl anion precursors that generate acyl anion equivalents under the promotion of cyanide anion via phosphonate-phosphate rearrangement. These anions readily react with aldehydes to provide cross-benzoin products. In this way it is possible to synthesize a variety of aromatic-aromatic, aromatic-aliphatic, and aliphatic-aromatic benzoins. Moreover the reaction of benzoylphosphonate with potent electrophile 2,2,2-trifluoroacetophenone provided the corresponding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(18 citation statements)
references
References 17 publications
0
17
0
1
Order By: Relevance
“…These products can be used for the generation of valuable acyl anion equivalents via phosphonate-phosphate rearrangement. 8 As a general extension of this work, we are currently investigating the asymmetric version of this reaction as well as addition reactions with TMS derivatives other than TMSCN.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These products can be used for the generation of valuable acyl anion equivalents via phosphonate-phosphate rearrangement. 8 As a general extension of this work, we are currently investigating the asymmetric version of this reaction as well as addition reactions with TMS derivatives other than TMSCN.…”
Section: Methodsmentioning
confidence: 99%
“…Acylphosphonate (1 mmol 8,15.2,(d,J = 5.7 Hz),15.4,(d,J = 5.8 Hz), 63.6 (d, J = 6.9 Hz), 64.2 (d,J = 7.6 Hz),70.4. 116.1,127.1,127.2,127.2,127.5,132.2,134.6.…”
Section: General Procedures For Tmscn Additionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Although significant progress has been made with enantioselective and intramolecular versions in recent years, [3] there still are limitations in the intermolecular coupling of two different aldehydes and of aldehydes with ketones. In these cases the outcome is typically a mixture of all possible symmetrical and unsymmetrical acyloins, with the chemoselectivity strongly depending on the relative thermodynamic stability of the corresponding products.[4] In order to overcome this problem several research groups have made excellent contributions by developing enzymatic approaches [5] or utilizing acylsilanes [6] and acylphosphonates [7] as acyl anion equivalents in cyanide-catalyzed transformations. In addition, very recently Scheidt et al reported intermolecular cross-acyloin reactions by fluoride-promoted addition of O-silylthiazolium salts.…”
mentioning
confidence: 99%
“…(3)]. [13] Furthermore, the strong basic catalysts potentially excluded the hydrophosphonylation of base-sensitive ketones, even mild bases such as tertiary amines may also cause side reactions.…”
Section: Highly Efficient Synthesis Of Quaternary A-hydroxymentioning
confidence: 99%